Assessment Of Malaysia Mobile Industry Response To Global Wireless Internet Challenges And Opportunities - Khong, Tan Too (2001)
The mobile technology has been envolving from a standard mobile people communication to the more complex multimedia communication. With this study , it is important to for local mobile company to revisit what are the areas to improve in order to gain the true benefits of Wireless Internet services.